Mitigating Wormhole Attacks’ Risks within Wearable Body Network - Goumidi, Mohammed Abdessamad; Zigh, Ehlem; Ali-Pacha, Adda Belkacem (IAES Indonesian Section, 2025)
In this research, we sought to develop a trust and secure routing protocol based on the Ad-hoc On-Demand Distance Vector (AODV) routing to combat wormhole attacks in Wearable Body Networks (WBNs), which integrates a routing strategy that leverages the path-checking method to detect and isolate paths affected by wormhole attacks effectively, it employs a routing technique that prioritizes nodes with the most heightened remaining energy during data transmission, along with a mixed cryptographic algorithm that combines the modified One Pad Time with the modified Affine ciphers to ensure safe transmission against malicious biosensor threats. Experimental findings indicate that our proposed protocol transcends the classic AODV routing protocol across all evaluation parameters, including packet delivery ratio, throughput, and energy consumption. Its primary advantage lies in considering multiple factors, like detecting unauthorized biomedical biosensors, efficient energy utilization in the network, and secure data transmission—differentiating it from other safe routing protocols. Moreover, the mixed encryption algorithm enhances efficacy and bolsters sensitive data security compared to classic cipher methods like the One Pad Time and Affine ciphers.